LiAlSiO4-coated Li1.2Mn0.54Ni0.13Co0.13O2 cathode: Enhancing Li-ion battery performance - Shang-Mei Yang; Shi-Ping Shao; Yu-Long Xie (PLoS ONE, 2025)
The lithium fast ion conductor LiAlSiO4 demonstrates exceptional lithium-ion transmission properties alongside remarkable chemical stability. Utilizing sol-gel techniques, we synthesized LiAlSiO4-coated cathode materials (LNCM@LASO) based on Li1.2Mn0.54Ni0.13Co0.13O2 to enhance their electrochemical performance. Rm space groups were identified in all materials through high-intensity diffraction peaks, indicating the presence of hexagonal layered α-NaFeO2 structures. Benefiting from the coating layer of LiAlSiO4, the conductivity and electrochemical performance of Li1.2Mn0.54Ni0.13Co0.13O2 are significantly improved. Compared with the unmodified LASO-0 sample (42.27%), the LASO-3 sample exhibits a superior initial coulomb efficiency of 66.02%. At various charge/discharge rates (0.1, 0.2, 0.5, 1, and 2 C), the LASO-3 electrode exhibits specific discharge capacities of 210.6, 189.3, 168.1, 151.8, and 125.2 mAh·g−1, correspondingly. Upon reverting the current density from 2 C to 0.1 C, the discharge capacity of the LASO-3 electrode rebounds to 206.4 mAh·g−1. After 100 cycles at 0.1 C, the LASO-3 electrode achieves a peak capacity retention rate of 88.9%. The superior conductive properties and chemical stability of the LNCM@LASO enhance the electron and ion transfer, thereby preventing electrolyte attack and boosting the electrochemical performance. This research marks a crucial step towards developing high-capacity, low-cost lithium-ion batteries with wide-ranging implications across multiple disciplines and industries.